Peace and Conflict: A Look at my Own Backyard - Steinmetz, Carl Hermann Dino (Advances in Social Sciences Research Journal, 2025)
This article examines peace and conflict through the lens of an autobiographical “backyard,” arguing that global transitions—ecological, geopolitical, socio-economic, and cultural—must be understood not only at macro and meso levels but also through the intimate micro-dynamics of individual experience. Situated within contemporary scholarship that frames the present era as one of profound systemic transformation, the study extends the author’s earlier work on peace and resistance by employing a methodology of critical self-assessment, or autoethnography. Through six guiding questions, the article interrogates encounters with aggression, violence, sexual harassment, deprivation, institutional racism, DARVO, and conflict across the author’s life course, spanning childhood in Indonesia, migration to the Netherlands, academic and professional trajectories, political activism, and the impact of personal tragedy. These narratives are analyzed through frameworks drawn from victimology, transcultural psychology, and power relations, illuminating how institutional structures reproduce exclusion, hierarchy, and racialization while also revealing the author’s evolving strategies of resistance—from physical self-defense and ethical refusal to organizational leadership, whistleblowing, and advocacy for vulnerable groups, migrants, and refugees. The discussion contrasts Western individualistic models of power and masculinity with communitarian non-Western philosophies such as Ubuntu, arguing that durable peace requires integrating these divergent epistemologies. A heuristic conflict model, F(C | PF–LA–PE) = VVPB & NE, is proposed to conceptualize conflict as relational, contextual, and structurally embedded. Ultimately, the article demonstrates that personal histories of conflict mirror broader global patterns shaped by colonial legacies, systemic discrimination, and structural violence. It concludes that any credible pursuit of world peace must incorporate micro-level experience as both analytical foundation and normative guide, recognizing the inseparability of individual, societal, and global dimensions of conflict and transformation.